Peran Ikatan Pekerja Sosial Masyarakat (IPSM) di Desa Sukamanis - Dea Dastara; Imam Budiharjo; Sani Mulyaningsih (Yayasan Literasi Sains Indonesia, 2022)
In society, we often encounter social problems. There is one social organization that can help deal with social problems in the community, namely the Community Social Workers Association (IPSM). IPSM is a forum for Community Social Workers (PSM) who have various important roles in society. There are several roles of Community Social Workers in Sukamanis Village, Kadudampit District, Sukabumi Regency, West Java Province, namely as initiators, motivators, dynamists, administrators, and brokers. This study used qualitative research methods. Data collection techniques in this study were conducted by interview and documentation. The results of this study indicate that the role of PSM in Sukamanis Village includes 5 roles, namely 1) Initiator, forming clean-up activities and encouraging the community to use the Health Insurance Administering Agency (BPJS) card and proposing the procurement of facilities and infrastructure for the Uninhabitable House program. (Rutilahu) both cash and non-cash to government and non-government institutions. 2) Motivator, providing encouragement and support to patients with Dengue Fever (DHF), skin diseases and other health problems. 3) Dynamizer, invites the surrounding community to work together and play an active role in overcoming social problems. 4) Administrator, helps handle and manage administration related to activating ID cards and BPJS so that when receiving assistance from the government it is right on target. 5) Broker, becomes a liaison to provide knowledge and understanding in completing the administrative coordination flow properly and correctly with related parties.